What are the appropriate methodological standards for international comparisons of health data? - Peter S. Hussey; Maria O. Edelen (BMC, 2018)
Abstract International comparisons of health systems are frequently used to inform national health policy debates. These comparisons can be used to gauge areas of strength and weakness in a health system, and to find potential solutions from abroad that can be applied locally. But such comparisons are methodologically fraught and, if not carefully performed and used, can be misleading. In a recent IJHPR article, Baruch Levi has raised concerns about the use of international comparisons of self-reported health data in health policy debates in Israel. Self-reported health is one of the most robust and frequently used measures of health, and the OECD uses a commonly accepted measure specification, which has five response categories. Israel's survey question, unlike the OECD measure specification, includes only four response categories. While this may be a valid method when applied over time as a scale within Israel, it creates problems for international comparison. To improve comparability, Israel's Central Bureau of Statistics could revise the survey question. However, revising the question would introduce a "break" in the data series that interrupts comparisons within Israel over time. Israeli policymakers therefore face a decision about priorities: is it more important to them to be able to track health status within Israel over time, or to be able to make meaningful comparisons to other countries? If the priority were international comparisons and the Israel survey was revised, a small study could be conducted among a sample of Israeli respondents to enable crosswalking of self-reported health responses from the four-point scale to the five-point scale. If the Central Bureau of Statistics does not revise its survey, the OECD should examine whether a stronger caveat is possible for its comparisons.